Dinamika Politik Identitas Etnis di Aceh (Studi Kasus Terhadap Kemenangan Irwandi-Nova Pada Pilkada 2017) - Nofriadi, Nofriadi; Afrijal, Afrijal; Nindiah, Isti (Jurnal Pemerintahan dan Politik, 2023)
This study explores the dynamics of ethnic identity politics in the 2017 regional elections (Pilkada) in Aceh, Indonesia. Identity politics, rooted in individuals’ awareness of their ethnic and religious affiliations, plays a significant role in Indonesia’s democratic development. The research uses identity politics theory, which explains individuals' alignment with specific racial, ethnic, religious, or cultural identities to form exclusive political alliances. A descriptive qualitative method is applied through library research, collecting data from academic literature, political regulations, and related sources. Findings indicate that ethnic identity politics remained a crucial factor in the 2017 Aceh elections. It was strategically utilized by candidates, particularly the Irwandi-Nova pair, to secure community support and ultimately achieve electoral victory. Their success was not solely due to ethnic identity appeals, but also because their programs were perceived as beneficial to the public. The pair gained significant voter support in regions with strong ethnic sentiments: 53.5% in Aceh Tengah, 53.2% in Bener Meriah, and 40.6% in Gayo Lues. The study concludes that while identity politics can be an effective political tool, its continued use risks fostering social division and intolerance. Therefore, future democratic practices should aim to minimize reliance on identity-based strategies to maintain social harmony.